Strategic Leadership of School Administrator under the Nakhonratchasima Secondary Education Service Area Office - Mungfaoklang, Chamrat; Kanongmat, Surawut; Kotchasit, Manatchai; Songnork, Prasong; Ratsantier, Boonrai (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Strategic leadership is the ability to set direction. Inspire Define the vision in line with environmental changes both inside and outside the organization by adhering to the goals and missions of the organization, as well as being able to convey and drive strategic management to succeed well. The objectives of this study are: 1) to Study the strategic leadership of educational administrators affiliated with the Secondary school's educational office in Nakhon Ratchasima province, and 2) to compare the strategic leadership of educational administrators affiliated with the Secondary schools' educational office in Nakhon Ratchasima province based on educational level and school size. Methodology: It is quantitative research. The population used in the research was 2,763 teachers of schools under the Nakhon Ratchasima Secondary Education Area Office in the academic year 2566 and 337 samples using the preliminary sampling method. The research tools used included questionnaires and statistical methods for data analysis, such as frequency, mean, percentage, standard deviation, F-test, and t-test. Results: (1) the overall digital leadership status of educational administrators is at a high level, and When considering each aspect, it was found that every aspect was at a high level. In order from most to least. The side with the highest average Ability to bring various input factors to determine strategy, followed by high-level thinking and understanding, and the aspect with the lowest average is the revolutionary thinking method. (2) Results of comparative analysis of opinions on the strategic leadership of educational institution administrators. Classified by educational level Both overall and each aspect are no different. The classification according to the size of the educational institution is significantly different at the .01 level. Conclusion: The research findings indicate that the strategic leadership profile of educational administrators is generally high both overall and across different dimensions. The average scores are highest in integrating various influencing factors into strategy formulation and lowest in revolutionary thinking. Comparisons based on educational levels and school sizes show no statistically significant differences at the .01 level, suggesting a consensus on leadership perceptions, irrespective of education levels and school sizes.